Body Image and Lifestyles of Obese Person, What is their Perception? - Fatin Hamimi Abdullah; Noridalis Maxtar; Yazreen Najihah; Nur Alisya Mat Udin; Osman Ali (Asian Journal of Medicine & Health Sciences, 2021)
Introduction: Obesity is a worldwide phenomenon affecting most the country in the world. It is associated with increase mortality and morbidity of the population. Malaysia has the incidence rate for obesity among the highest in the region. Objectives: The aim of this study is to determine the perception of obese person in RCMP on their body image and their lifestyles. Methodology: A cross-sectional study was conducted using a structured questionnaire among 30 selected students and staffs of the RCMP, Ipoh. Respondents visually obese will be selected after getting the consent, BMI will be measured to confirm the diagnosis. Data on their perception to body image and lifestyles, eating habits, physical activity was collected. Results: Out of these 30 obese people, 47% did not perceive that they were obese. More than half (57%) also found to have a poor self - perception on their lifestyles. Most of the respondents (73.3%) did not perform any exercise. Nevertheless, high percentage of these samples were following healthy eating habits. However, no significant association was found between perception on body image and lifestyles with age, gender, marital status, eating habits and physical activities of these obese people. Conclusion: The study has shown that half of the obese person in this study did not aware or felt that they were obese. Quite high percentage of them had poor perception on lifestyles and did not practice healthy lifestyles to prevent the disease and its associated morbidity. A study with bigger samples size is needed to confirm the relationship and come up with innovative program to prevent the disease.